2021
DOI: 10.1007/s00300-021-02818-3
|View full text |Cite
|
Sign up to set email alerts
|

Crude oil exposure reduces ice algal growth in a sea-ice mesocosm experiment

Abstract: Oil production in Arctic ice-covered areas poses a risk for pollution of the ecosystem including that within the brine channel network of sea ice. Sea-ice autotrophs contribute substantially to Arctic primary production, but are inherently difficult to test for oil exposure responses in situ. This study had two objectives, first, we developed a suitable lab-based mesocosm system, second, we tested oil effects on sea-ice algae. Specifically, we investigated if Alaska North Slope crude oil exposure reduces ice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…After release the droplets can travel several hundred square kilometres within several days (Berenshtein et al, 2020) and are exposed to weathering processes that continually decrease the droplet size (e.g. Daling et al, 1990;Resby and Wang, 2004;Dilliplaine et al, 2021). The dispersed droplet distribution sizes can be described by a log-normal distribution of submicrometre droplets with an experimentally measured peak for weathered oil centred around a median radius of 0.05 µm (Otremba, 2007;Li et al, 2011;Johansen et al, 2013;Haule et al, 2015;Haule and Freda, 2016).…”
Section: Droplet Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…After release the droplets can travel several hundred square kilometres within several days (Berenshtein et al, 2020) and are exposed to weathering processes that continually decrease the droplet size (e.g. Daling et al, 1990;Resby and Wang, 2004;Dilliplaine et al, 2021). The dispersed droplet distribution sizes can be described by a log-normal distribution of submicrometre droplets with an experimentally measured peak for weathered oil centred around a median radius of 0.05 µm (Otremba, 2007;Li et al, 2011;Johansen et al, 2013;Haule et al, 2015;Haule and Freda, 2016).…”
Section: Droplet Size Distributionmentioning
confidence: 99%
“…As oil is released into seawater it is influenced by several weathering processes: evaporation, dispersion, wave action, sedimentation, photo-oxidation, and bioremineralisation (e.g. Daling et al, 1990;Resby and Wang, 2004;Dilliplaine et al, 2021). The physicochemical properties of oil (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a shows the initial uniform cooling of the saline solution before the freezing point was reached. 2007), Gully and others (2007), Bullock and others (2017), Oggier and others (2019), Dilliplaine and others (2021) University of Alberta Cold Room Facility n/a n/a Artificial sea…”
Section: Sea Ice Physical Propertiesmentioning
confidence: 99%
“…The third was a three year collaboration between SINTEF and the Research Council of Norway looking at the 'Fate, Behaviour and Response to Oil Drifting into Scattered Ice and Ice Edge in the Marginal Ice Zone' (Singsaas et al, 2020). Smaller studies have looked into the hyperspectral features of oil-polluted sea ice (Liu et al, 2018) and the effects of exposure to crude oil on ice algae (Dilliplaine et al, 2021). In another study, Gavrilo and Tarashkevich (1992) found that crude oil can migrate vertically through multiyear ice if it is pumped either into or below the ice.…”
Section: Introductionmentioning
confidence: 99%